1997
DOI: 10.1210/me.11.6.693
|View full text |Cite
|
Sign up to set email alerts
|

The Partial Agonist Activity of Antagonist-Occupied Steroid Receptors Is Controlled by a Novel Hinge Domain-Binding Coactivator L7/SPA and the Corepressors N-CoR or SMRT

Abstract: Steroid receptor antagonists, such as the antiestrogen tamoxifen or the antiprogestin RU486, can have inappropriate agonist-like effects in tissues and tumors. To explain this paradox we postulated that coactivators are inadvertently brought to the promoters of DNA-bound, antagonist-occupied receptors. The human (h) progesterone receptor (PR) hinge-hormone binding domain (H-HBD) was used as bait in a two-hybrid screen of a HeLa cDNA library, in which the yeast cells were treated with RU486. We have isolated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(127 citation statements)
references
References 0 publications
3
121
1
2
Order By: Relevance
“…This corepressor, termed RTA, was shown to interact with the N-terminal domain of ERs. With regard to coactivators, in addition to the p160 coactivators, one coactivator that affects tamoxifen activity has been reported, but there is no information on ERa or tamoxifen specificity of this coactivator [52]. In the present study, we demonstrated that menin can bind to AF-2, and tamoxifen inhibits the binding of menin to ERa, but tamoxifen suppressed ERE-luciferase activity only to the levels of nontreated wild-type MCF-7 in menin-overexpressing clones.…”
Section: Discussionsupporting
confidence: 41%
“…This corepressor, termed RTA, was shown to interact with the N-terminal domain of ERs. With regard to coactivators, in addition to the p160 coactivators, one coactivator that affects tamoxifen activity has been reported, but there is no information on ERa or tamoxifen specificity of this coactivator [52]. In the present study, we demonstrated that menin can bind to AF-2, and tamoxifen inhibits the binding of menin to ERa, but tamoxifen suppressed ERE-luciferase activity only to the levels of nontreated wild-type MCF-7 in menin-overexpressing clones.…”
Section: Discussionsupporting
confidence: 41%
“…NCoR/SMRT have also been reported to partner with HDAC4, HDAC5, and HDAC7 [74,75]. Steroid hormone receptors do not appear to interact with NCoR or SMRT in the presence or absence of agonists, whereas both the ER and the progesterone receptor can interact with these corepressors in the presence of their respective antagonists [80][81][82][83]. Interestingly, NCoR/ SMRT are also known to mediate transcriptional repression from a wide variety of other non-receptor-mediated pathways.…”
Section: Ncor/smrt/hdacsmentioning
confidence: 99%
“…Extrapolation from this analogy is that the proteins (corepressors and/or HDACs) recruited by cortisol-bound GR are likely to be different, quantitatively and/or qualitatively, from those by RU486-bound GR in inducing GR-mediated transrepression, but similar to those recruited by dexamethasone-bound GR. This explanation has been suggested for the agonist function of RU486 in PR function [15] and for the agonist function of tamoxifen in estrogen receptor function [38]. The recruitment by RU486-bound GR is more sensitive to GR density changes than cortisol-bound GR, suggesting that RU486-bound GR has a greater degree of conformation-dependent functional variability in cell type-dependent agonist action for transrepression.…”
Section: Discussionmentioning
confidence: 87%